1984
DOI: 10.1172/jci111480
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of human diploid fibroblast collagen synthesis by interferons.

Abstract: Abstract. The effects of a-and -interferons (IFNs) on collagen production by confluent human diploid fibroblasts in culture were examined. It was found that partially purified a-IFNs and affinity purified -y-IFNs caused >50% inhibition of collagen synthesis by these cells independently of their effect on cell proliferation. Recombinant a-IFNs showed a similar effect (38.8% inhibition), indicating that collagen synthesis inhibition was a constitutive property of IFNs. Collagen synthesis inhibition by IFNs was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
162
0
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(172 citation statements)
references
References 12 publications
8
162
0
2
Order By: Relevance
“…[32][33][34][35] In vivo models of enhanced collagen synthesis have also revealed that IFN-g reduces the collagen accumulation associated with foreign bodies, skin wound healing and bleomycin-induced lung AcMNPV-mediated IFN alleviates LC in a murine model Y Nishibe et al fibrosis. [36][37][38] Further, in liver fibrosis induced by Schistosoma mansoni infection, IFN-g significantly reduces collagen accumulation, and type I and III procollagen mRNA levels.…”
Section: Ifn Inductionmentioning
confidence: 99%
“…[32][33][34][35] In vivo models of enhanced collagen synthesis have also revealed that IFN-g reduces the collagen accumulation associated with foreign bodies, skin wound healing and bleomycin-induced lung AcMNPV-mediated IFN alleviates LC in a murine model Y Nishibe et al fibrosis. [36][37][38] Further, in liver fibrosis induced by Schistosoma mansoni infection, IFN-g significantly reduces collagen accumulation, and type I and III procollagen mRNA levels.…”
Section: Ifn Inductionmentioning
confidence: 99%
“…IFN-γ is a major mediator of resistance against a wide range of pathogens through macrophage activation (reviewed by Murray, 1988). On the other hand, IFN-γ in vitro inhibits the synthesis of type I collagen by human fibroblasts (Jimenez et al, 1984) and by human myofibroblastc Ito cells (Mallat et al, 1995). Moreover, an in vivo treatment with IFN-γ decreases collagen deposition and types I and III procollagen mRNA levels in the liver of S.mansoni-infected mice (Czaja et al, 1989).…”
Section: H Uman Alveolar Echinococcosis Caused Bymentioning
confidence: 99%
“…Alternatively, it could be that interferon-x has less effect on matrix production than the other interferons. Experiments with isolated cells show this to be true for fibroblast collagen synthesis, both on the protein (Jimenez et al, 1984;Duncan and Berman. 1985) and the mRNA level (Duncan et al.…”
Section: Discussionmentioning
confidence: 84%